The environmental risk assessment for decision support system for water management in the vicinity of open cast mines (DS WMVOC) - Kochanek, Krzysztof; Tynan, Suzanne (Technological and Economic Development of Economy, 2010)
The paper presents risk assessment methodology used within a Decision Support System for Water Management in the Vicinity of Open Cast Mines (DS WMVOC). The DSS was designed to aid in decision making regarding ground and surface water resources, by two potentially conflicting stake holders in Konin county (Central Poland) that is, the County Administration and the open pit mine industry. Estimates of potential changes in groundwater head are achieved by numerical modelling of the groundwater system in which the open cast mines and receptors are located. The evaluation of spatially and time‐distributed environmental risk is obtained by means of GIS supported Monte Carlo methodology. Calculations can be run in the DS WMVOC resulting maps of the risk to different receptor types, and maps of relative risk for different abstraction or dewatering scenarios, as well as an overall risk value for the region. Estimation of the magnitude of any adverse impact is related to the element (type of receptor) being impacted and a sensitivity rating has been devised for each receptor type. The risk estimation methodology implemented in the DS WMVOC was illustrated by analysis of two hypothetical groundwater management scenarios. Article in English. Rizikos aplinkai vertinimas naudojant netoli atvirųjų kasyklų esančių vandens išteklių valdymo sprendimų paramos sistemą Santrauka. Straipsnyje pateikiama rizikos vertinimo metodika, naudojama netoli atvirųjų kasyklų esančių vandens išteklių valdymo sprendimų paramos sistemoje. Sprendimų paramos sistema (SPS) buvo sukurta siekiant priimti naudingus sprendimus, priešingus interesų turinčioms šalims, dėl požeminio ir paviršinio vandens išteklių. Konino regione (Vidurio Lenkija) konfliktuojančios pusės yra apskrities administracija ir atvirų kasyklų pramonės įmonė. Galimi požeminio vandens lygio pokyčiai įvertinami atliekant skaitmeninį požeminio vandens sistemos modeliavimą. Rizika aplinkai erdvės ir laiko požiūriu vertinama taikant GIS ir Monte Karlo metodologiją. Skaičiuojant sprendimų paramos sistema sudaro specialius rizikos žemelapius, atlieka bendra rizikos įvertinimą regione. Sprendimų paramos sistemoje įdiegta rizikos vertinimo metodologija pritaikyta analizuoti du hipotetinius požeminio vandens valdymo scenarijus. Reikšminiai žodžiai: sprendimų paramos sistema (SPS), GIS, rizikos įvertinimas, atvirosios kasyklos, požeminio vandens modeliavimas. First published online: 10 Feb 2011